Form teachers’ perceptions of the need for in-service training to manage their students’ problematic behaviour - Zemančíková, Vladimíra (Sodobna pedagogika, 2025)
This study aimed to identify Slovak form teachers’ educational needs to manage their students’ problematic behaviour. To this end, a custom questionnaire was developed and offered to form teachers in lower secondary education (ISCED2) and upper secondary education (ISCED3) (N = 266). Their views were then compared based on the type of schools they worked in, their years of experience, and their gender. The Kruskal-Wallis and Dunn’s post-hoc tests were then conducted, which revealed significant differences in the educational needs of those with different years of experience and those who work in different types of school: on average, the form teachers with more than 15 years of experience reported a lower need for in-service training than those with less experience, and the form teachers in four-year gymnasiums reported a lower need than the primary school (ISCED2 level) and secondary vocational school teachers (ISCED3 level).
Keywords: education; form teacher; izobraževalne potrebe učiteljev; pedagogika; pedagogy; problem behaviour of students; problematično vedenje učencev; profesionalni razvoj učiteljev; razrednik; teacher professional development; teachers’ educational need; vzgoja in izobraževanje